Moulting patterns of Alabio and Mojosari ducks and their relation on blood lipids (tryglycerides), egg production and egg quality - Maijon Purba; P.S Hardjosworo; L.H Prasetyo; D.R Ekastuti (Indonesian Center for Animal Research and Development (ICARD), 2005)
Moulting is a biological condition that can happen in poultry. It is resulted from the complex interaction which involves the function of thyroxine hormone. Moulting can reduce or even stop the egg production. A study was conducted to observe the moulting patterns of local ducks (Alabio and Mojosari) and to determine the relation of moulting with blood lipids (triglycerides), egg production and quality. Each breed consisted of ten female dukcs were observed for moulting pattern, blood triglycerides, egg production and quality. Fourty ducks were used for simulation of egg production. Data from moulting patterns,egg production and quality were analyzed using t-based on Least Square means with Statistical Analysis System. The relation of breeds and moulting patterns with triglycerides were analyzed using Analysis of Variance (ANOVA) for a completely randomized design in a factorial arrangement of 2x2. The main factor was kind of breeds, while the subfactor was the period of moulting, before and during moulting. There were not interaction in every variables between both factors. The average moulting periode of Alabio was significantly (P<0.05) shorter than that of Mojosari (69 vs 76 days). There were 40% of Alabio ducks moulting for 61-70 days, while 40% of Mojosari ducks moulting for 71-80 days. Egg production of Alabio ducks before and after moulting were higher than those Mojosari ducks. The triglycerides content of Alabio and Mojosari ducks was decreased during moulting, in Alabio ducks they were 32.02 and 27.64 μg/ml before and during moulting, while in Mojosari ducks they were 32.83 and 29.32 μg/ml respectively. Egg weight, albumin weight, yolk weight, and haugh unit of the two breeds increased after moulting, while yolk colour decreased. The average yolk colour of Alabio ducks before and after moulting were 6.90 and 5.11, while in Mojosari ducks they were 7.90 and 4.60 respectively. Key Words: Moulting, Tryglycerides, Egg Productivity, Egg Quality